Islamic Natural Law Theories: By Anver M. Emon (New York: Oxford University Press, 2010. hbk. 222 pages) (American Journal of Islam and Society, 2011)
Emon’s Islamic Natural Law Theories, is an excellent source of researchfor specialists in Islamic jurisprudence. It is not for the general public.Emon divides his work into five chapters: Introduction, Hard Natural Law,The Critique of Hard Natural Law, Soft Natural Law, and Conclusion. Bothhis style and his usage of words are fascinating. His understanding of thepremodern works on Islamic jurisprudence (usul al-fiqh) reflects his indepthresearch and comprehension of classical works. His rendering of jurisprudentialterms (alfaz usuliyyah) into English language also marks hisgreat familiarity with Islamic sources. This work is an excellent addition tothe literature on Islamic law.Emon’s work focuses on the ontological authority of reason in theShari‘ah. He investigates the use of reason in establishing a rule of lawalongside the source texts. He explicates the meanings of natural law asunderstood by premodern jurists and explains to what extent, in the absenceof source texts, can good and bad (husn and qubh) assume sufficientnormative authority, which will result in Shari‘ah obligation.Emon affirms that the use of reason in Shari‘ah has been debated extensivelyby Muslim jurists. While many scholars rejected the authority ofreason in legislation, others endorsed it. However, in practice, all scholarsresort to it in one form or another. From chapter one to the end, Emon successfullyexplains with lucidity the concept of good and bad. He analyzesthis concept from the perspectives of major Muslim scholars from differentschools of Islamic jurisprudence. He selects leading scholars from eachschool ‒ like Qadi Abdul Jabbar, Abu Husayn al-Basri, Abu Bakr al Jassas,al-Ghazali, al-Qarafi, al-Shatibi, Ibn Hazm al-Zahiri, and others ...